(untitled) (Biological Sciences - PJSIR, 2022)
Pollution is the biggest concern nowadays in which aquatic pollution is on top. Many xenobiotic components are responsible for causing the pollution in aquatic ecosystem due to their high toxicity and endurance in the environment. In the present study pernicious effects of synthetic pyretheroid pesticides (Cypermethrin and Lambda-cyhalothrin) on the marine fish (Oreochromis mossambicus) was studied. Toxicity of the pesticide on marine organism was estimated by determination of the 24 h LC50. The toxicity tests were performed separately for each pesticide. Data generated from the acute toxicity tests were evaluated using the probit analysis statistical method. After the exposure of fish to the pesticides the LC50 values were estimated which were showing that both the chemicals have lethal effect on the fish. Concentration of pesticide is directly proportional to the mortality rate of the fish. The investigation shows that the pyrethroid pesticides have lethal effects.